Unveiling the role of hexon-associated host proteins in fowl adenovirus serotype 4 replication - Zhang, Xiaojun; Wang, Xueping; Zhao, Yina; Li, Shifan; Xu, Xingang (Frontiers in Veterinary Science, 2025)
Fowl adenovirus serotype 4 (FAdV-4), a member of the family Adenoviridae and the genus Aviadenovirus, is responsible for a significant number of emerging diseases that cause substantial economic losses in the poultry industry worldwide. The hexon protein plays a crucial role in inducing autophagy and apoptosis and promoting virus replication. Identifying host factors that interact with the hexon protein is essential for elucidating the pathogenesis of FAdV-4. In this study, tandem affinity purification followed by mass spectrometry (TAP/MS) was used to screen the interacting proteins of hexon in leghorn male hepatoma (LMH) cells for the first time. A total of 82 hexon-associated proteins were identified in LMH cells expressing hexon compared with cells expressing the empty vector (NC). Gene Ontology and Ingenuity Pathway Analysis provided functional annotations of the hexon-interacting proteins and revealed that these proteins were associated with multiple biological functions, including virus infection, the cell cycle, endocytosis and the phagosome. Western blot and coimmunoprecipitation validation tests revealed that randomly selected significant proteins (CCT5, CCT7, and HSP70) interact with hexon, and these results are consistent with those of TAP/MS. Among them, the overexpression of CCT5 inhibited virus replication, whereas blocking CCT5 increased virus replication. In conclusion, this study demonstrated the successful screening of host proteins interacting with the hexon protein. The findings of this study will lead to a better understanding of the molecular mechanisms of hexon, thus benefiting the development of effective antiviral strategies.